El sistema de control interno y su incidencia en la mejora de la gestión de Almacén de la Empresa Constructora Corporación OMEGA Contratistas Generales S.A.C. - Florian Rivera, Sandra Evelyn (2016)
This research paper called "The internal control system and its impact on improving warehouse management of the construction company Corporacion Omega General Contractors SAC" which, the problem was about how affects a system of internal control in the improving management warehouse of the company in question, the main objective was to determine the incidence of internal control system to improve the efficiency of warehouse management of the construction company Omega Corporation General Contractors SAC. The development of this research was carried out from a population of medium-sized construction of parks and roads in the province of Trujillo which the sample was the company called “Corporacion Omega Contratistas Generales SAC”. The research was applied with type of pre - experimental design. It was concluded that the internal control system has a positive effect on improving warehouse management company Omega Corporation General Contractors SAC because it has achieved to organize and improve policies and processes in addition to dwindle risks.